2018
DOI: 10.1021/acs.jmedchem.8b00650
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) Inhibitors: Hit to Lead Optimization of Systemic Agents

Abstract: The optimization of a new class of small molecule PCSK9 mRNA translation inhibitors is described. The potency, physicochemical properties, and off-target pharmacology associated with the hit compound (1) were improved by changes to two regions of the molecule. The last step in the synthesis of the congested amide center was enabled by three different routes. Subtle structural changes yielded significant changes in pharmacology and off-target margins. These efforts led to the identification of 7l and 7n with ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…We also compared our present PF846 results with the 21 PF846 targets previously identified in Huh-7 cells (S3D Fig and S2 Table) and observed that changes in the read count 3' of the stall site defined by DMax were highly correlated between experiments (Pearson R=0.82), showing the high reproducibility of our method of analysis (S2 Fig). However, we found that the main stall site position seen in the ribosome profiling read-counts varied slightly when comparing the present PF846 Liaud et al 9 treatment and the previously published PF846 data [10], and when comparing PF8503 and PF846 stall sites on common targets (S4 Fig, S1 Table and S2 Table). This could be due to technical variability in the preparation of the ribosome profiling libraries, such as the efficiency of RNAse I digestion.…”
Section: Ribosome Profiling To Identify Proteins Targeted By Pf8503mentioning
confidence: 51%
See 4 more Smart Citations
“…We also compared our present PF846 results with the 21 PF846 targets previously identified in Huh-7 cells (S3D Fig and S2 Table) and observed that changes in the read count 3' of the stall site defined by DMax were highly correlated between experiments (Pearson R=0.82), showing the high reproducibility of our method of analysis (S2 Fig). However, we found that the main stall site position seen in the ribosome profiling read-counts varied slightly when comparing the present PF846 Liaud et al 9 treatment and the previously published PF846 data [10], and when comparing PF8503 and PF846 stall sites on common targets (S4 Fig, S1 Table and S2 Table). This could be due to technical variability in the preparation of the ribosome profiling libraries, such as the efficiency of RNAse I digestion.…”
Section: Ribosome Profiling To Identify Proteins Targeted By Pf8503mentioning
confidence: 51%
“…The same experiment and pipeline was used in parallel with PF846 in order to compare our results to previously published data [10]. After using the bioinformatic pipeline described previously [9] (S2A Fig), we found that PF8503 affected the translation of 46 mRNAs, whereas PF846 affected translation of 24 mRNAs after 1 hr of Liaud et al 8 treatment. As expected PCSK9 was affected by both compounds with a log 2 fold change of -1.5 and -2 for PF8503 and PF846, respectively (Fig 1C and S1 Table).…”
Section: Ribosome Profiling To Identify Proteins Targeted By Pf8503mentioning
confidence: 62%
See 3 more Smart Citations